I have a sequence $(a_n)_{n=1}^\infty$ with the following properties:

Monotonically decreasing

$a_n \geq 0$

$\sum_{n=1}^\infty a_n < \infty$

I have to show

$$\lim_{n \rightarrow \infty} n \ a_n = 0$$

My thoughts:

By theorem 3.23 in baby Rudin, if $\sum_{n=1}^\infty a_n < \infty$ then $\lim_{n \rightarrow \infty} a_n = 0$

Therefore, if I can show that $\sum_{n=1}^\infty n a_n < \infty$ then $\lim_{n \rightarrow \infty} n a_n = 0$

By theorem 3.24 in baby Rudin, A series of nonnegative terms converges if and only if its partial sums form a bounded sequence. So, I need to prove the sequence $n \ a_n$ has only nonnegative terms and the partial sum $\sum_{k=1}^n k a_k$ is bounded.

Now, the partial sum of n is bounded. By theorem 3.14 in baby Rudin, If the sequence $a_n$ is monotonic then the sequence converges iff it is bounded. I conclude $a_n$ is bounded. So if the sequence $a_n$ is bounded, it partial sum will be bounded.

Next, the product of two bounded series is bounded

$$\sum_{k=1}^n k \ \sum_{k=1}^n a_k = \sum_{k=1}^n k a_k \leq M$$


Any ideas?

  • $\begingroup$ Showing that $\sum_{n=1}^\infty na_n < \infty$ is a bit strong. For example, the sequence $a_n = \frac1{n^2}$ satisfies your conditions, but $\sum_{n=1}^\infty na_n = \infty$ $\endgroup$
    – Mathmo123
    Oct 26 '14 at 18:22

$$na_n=2\sum_{k=n/2}^na_n\leqslant2\sum_{k=n/2}^na_k\leqslant2\sum_{k=n/2}^\infty a_k\to0$$


Let $\displaystyle S_N = \sum_{n=1}^N a_n$. Since $a_n \ge 0$, we have $$\frac{S_N}N \le \frac1N\sum_{n=1}^\infty a_n\to0\ \text{ as }N\to \infty$$ But $$\begin{align} S_N &\ge\sum_{n=1}^Na_N \quad\text{since $a_n$ is monotonically decreasing}\\&=Na_N\end{align}$$Therefore, $$0\le a_N \le \frac{S_N}N\to0$$

  • We have $a_{1} > a_{2} > a_{3} > \cdots >a_{n} > a_{n+1} > \cdots$

  • $S_{n} = \sum_{k=1}^{n} a_{k}$. Then we have $\displaystyle\lim_{n \to \infty} a_{n}=0$ since $\sum_{n}a_{n}<\infty$

  • $S_{2n}=a_{1} + a_{2} + \cdots + a_{2n} = S_{n}+ a_{n+1} + a_{n+2} + \cdots +a_{2n} > S_{n}+n\cdot a_{2n}$

  • $0 < n \cdot a_{2n} < S_{2n}-S_{n}$ gives $\displaystyle \lim_{n \to \infty} n\cdot a_{2n}=0 \implies\lim_{n \to \infty} 2n \cdot a_{2n}=0$.

  • Similarly one can show $\displaystyle\lim_{n\to\infty} (2n+1)\cdot a_{2n+1}=0$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.